2012
DOI: 10.1186/1471-244x-12-16
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a cognitive-behavioral therapy (CBT) manualized program for clinically anxious children: study protocol of a randomized controlled trial

Abstract: BackgroundIn the Netherlands, the prevalence of anxiety disorders is 20%; and children with anxiety are at increased risk for psychopathology throughout adulthood. Recently, a revised version of a cognitive behavioral therapy manualized program called 'Thinking + Doing = Daring' (TDD) was developed for children between 8 and 12 years old with an anxiety disorder. The main aim of this project is to conduct a Randomized Controlled Trial (RCT) to evaluate the effectiveness of TDD.Methods/DesignThe CBT program wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The data in this study originated from a larger study (Jansen et al 2012 ) which investigated the effectiveness of an individual CBT program called Thinking + Doing = Daring ( Denken + Doen = Durven ; Bögels 2008 ). In the current study, three groups were initially planned to be investigated: Participants in the clinically anxious group (1) were 81 mothers and 55 (68%) fathers of clinically referred children with an anxiety disorder.…”
Section: Methodsmentioning
confidence: 99%
“…The data in this study originated from a larger study (Jansen et al 2012 ) which investigated the effectiveness of an individual CBT program called Thinking + Doing = Daring ( Denken + Doen = Durven ; Bögels 2008 ). In the current study, three groups were initially planned to be investigated: Participants in the clinically anxious group (1) were 81 mothers and 55 (68%) fathers of clinically referred children with an anxiety disorder.…”
Section: Methodsmentioning
confidence: 99%
“…Autoimmune disease, for example rheumatoid arthritis, is also associated with markedly elevated risk of depression (Margaretten et al, 2011a; Covic et al, 2012). Notably, there appears to be a strong correlation between the severity of rheumatoid arthritis and the incidence of depression, with a recent meta-analysis demonstrating that those with the most severe form of arthritic disease have a six-fold higher incidence of depression relative to those with the mildest form Godha et al (2010).…”
Section: Systemic Disorders Associated With Depressionmentioning
confidence: 99%
“…Children were given small gifts for participating in the study, and families received €15 after completing the postassessment. Ethical approval has been granted for the original study of Jansen et al () by the ethical committee of the Faculty of Social Sciences, Radboud University ( ECG16122010 ).…”
Section: Methodsmentioning
confidence: 99%
“…The general aim of this study was to investigate changes in children's communication patterns and whether these changes were associated with successful treatment outcomes in children with anxiety following a protocolized CBT program. Data were taken from a randomized controlled trial in which the effectiveness of the manualized CBT program developed by Bögels () was evaluated against treatment as usual (see Jansen et al, , for study protocol and Van Doorn, Jansen, Bodden, Lichtwarck‐Aschoff, & Granic, , for outcomes). The data were collected at Dutch mental health care agencies between January 2012 and January 2014, and results showed that the CBT program was generally effective although outcomes did not differ between conditions (Van Doorn et al, ).…”
Section: Current Studymentioning
confidence: 99%